Origanum dubium Boiss. (Cypriot oregano) Use for the Preservation of Fresh Spearmint Quality and Safety - Xylia, Panayiota; Chrysargyris, Antonios; Tzortzakis, Nikos G. (My University, 2024)
Very little is known about the preservation and storage of fresh medicinal and aromatic plants (MAPs) and/or herbs. As with many leafy vegetables, i.e., lettuce, fresh spearmint is a very perishable product throughout the production line and requires special handling/processing. The current study aimed to examine the antibacterial activity of selected MAPs (Origanum dubium, Salvia fruticosa and Sideritis cypria) grown in Cyprus towards foodborne pathogens. Then, the most effective MAPs’ essential oil (EO) and hydrosol (at different doses; combination of concentration and time of dipping submerge) were tested to preserve fresh spearmint quality and safety. The results showed that O. dubium EO and hydrosol presented great in vitro antibacterial activity against four foodborne pathogens and those products were further selected for application on fresh spearmint. During sensory evaluation, it was observed that higher O. dubium EO concentrations and longer time of application resulted into a less marketable product (less acceptable with less spearmint-like aroma), while hydrosol resulted in a more marketable product even at high doses. In general, EO and hydrosol applications increased spearmint’s antioxidants (including polyphenols, flavonoids, and ascorbic acid), resulting in a product of increased nutritional value. The bacterial populations of Salmonella enterica and Listeria monocytogenes inoculated on fresh spearmint were decreased with the EO and hydrosol application doses applied, and their effects were evident even after six days of storage at 4 °C. From the findings of this study, it can be concluded that O. dubium EO and hydrosol could be a potential sanitation method for fresh spearmint preservation.
Keywords: essential oil; food safety; natural products; Origanum dubium; postharvest quality; spearmint